Dynamic Nanocomposite Microgel Assembly with Microporosity, Injectability, Tissue‐Adhesion, and Sustained Drug Release Promotes Articular Cartilage Repair and Regeneration. Issue 8 (15th December 2021) - Feng, Qi; Li, Dingguo; Li, Qingtao; Li, Shuxian; Huang, Hanhao; Li, Haofei; Dong, Hua; Cao, Xiaodong
Abstract: Owing to the lack of blood vessels, nerves, and lymph, articular cartilage defect is difficult to self‐repair. Although several cartilage tissue engineering products have been authorized for clinical use, there are still some problems such as large surgical wounds, weak adhesion with the host tissue, and the limited source of autologous chondrocytes. In this paper, a novel dynamic nanocomposite microgel assembly with excellent microporosity, injectability, tissue‐adhesion, and sustained kartogenin (KGN) release is reported. Specifically, KGN‐loaded cyclodextrin nanoparticles are synthesized through nanoemulsification and incorporated into bone marrow mesenchymal stem cell (BMSCs)‐laden microgels via droplet‐based microfluidics and photo‐crosslinking, which are then bottom‐up assembled via dynamic crosslinking between dopamine‐modified hyaluronic acid and phenylboronic acid groups on microgel surface. Results reveal that the microgel assembly can avoid the cell endocytosis of nanoparticles, ensure the high BMSC viability during the regular cell culture, cryopreservation and injection process, promote the chondrogenic differentiation of BMSCs. In addition, animal expriment proves the newborn cartilages present the typical characteristics of articular cartilage. In brief, this microgel assembly not only offers convenience for clinical use (injectability, tissue adhesion) but also provides good microenvironments for chondrogenesis (controlled drug release, interconnected micropores), indicative of its promising application for cartilage repair and regeneration. Abstract : A novel dynamic‐crosslinked and drug‐loaded microgel assembly is designed from the view of scaffold construction and physicochemical microenvironment creation, which exhibits the properties of injectability, tissue adhesion, sustained kartogenin release, and interconnected micropores structure. The microgel assembly can be injected into defects, integrate with host tissue, offer proper physicochemical microenvironment, and eventually promote articular cartilage repair and regeneration.